GNU: a strategy to foster democracy?: a case study of Zimbabwe’s 2008 Government of National Unit - Samunderu, Elvis (Midlands State University, 2018)
The predominant discourse around Governments of National Unity (GNUs) in Africa involves the role they play towards ushering nations from dire political situations to a more democratic dispensation. Contemporary studies on African GNUs highlight that these governments have been utilised to serve as conflict resolution mechanisms and they have realised much success in pacifying violent situations. This study seeks to explore into the 2009-2013 Government of National Unity (GNU) that was employed in Zimbabwe with distinct attention to the extent it managed to usher Zimbabwe towards a more democratic order. The study assesses how effective and sustainable the Government of National Unity was in advancing and endorsing the democratic agenda in Zimbabwe. The study exhibits that though the 2009 Zimbabwean GNU realised some democratic virtues during its tenure, it could not assure continuity of these virtues after its tenure lapsed and in some instances the GNU alone could not address important issues owing to its inherent limitations, as such the study examines these limitations. In an attempt to gauge the margin of lag with regards to democracy in Zimbabwe, the study challenges whether Zimbabwe had been operating within the framework of democracy or otherwise since its independence in 1980.